Peanut oral immunotherapy: current trends in clinical trials. Issue 1 (31st January 2022) - Reinwald, Simone; Rolland, Jennifer M; O'Hehir, Robyn E; van Zelm, Menno C
Abstract: Immunotherapy for allergy has been practiced for over 100 years. Low-dose repeated exposure to specific allergen extracts over several months to years can successfully induce clinical tolerance in patients with allergy to insect venoms, pollen, house dust mite, and domestic animals. Different regimens and routes for immunotherapy include subcutaneous, sublingual, oral, and intralymphatic. Food allergies have been difficult to treat in this way due to high anaphylactic potential and only recently the first immunotherapy for peanut allergy has received regulatory approval. Several clinical trials have indicated high efficacy in desensitisation of peanut-allergic individuals using oral immunotherapy, which allows for safer administration of relatively high allergen concentrations. Still, the risk of adverse events including serious allergic reactions and high anxiety levels for patients remains, demonstrating the need for further optimisation of treatment protocols. Here we discuss the design and outcomes of recent clinical trials with traditional oral immunotherapy, and consider alternative protocols and formulations for safer and more effective oral treatment strategies for peanut allergy.